Interactive E-Module on Perimeter and Area of Plane Figures Based on Balinese Ethnomathematics to Enhance the Creativity Skills - Marheni, Kadek Rizka; Suarjana, I Made; Paramita, Made Vina Arie (MIMBAR PGSD Undiksha, 2024)
Implementation of the mathematics learning process using conventional book teaching materials provided by the government and teachers who do not have enough time to develop teaching materials will affect students' learning creativity and students' understanding of mathematics material. The conventional learning process results in the formation of abstract concepts so that students' creativity in identifying and solving problems is less than optimal. The aim of the research is to develop an e-module for interactive material on the circumference and area of flat figures based on Balinese ethnomathematics that is valid, practical and effective to increase the creativity of fifth grade elementary school students. The research was conducted using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The subjects of this research were learning materials experts, learning media experts, 2 practitioners/class teachers and 23 students in class VB SD No. 1 Strait. The research results show that (1) the validity of learning material experts is worth 4.75 with very good qualifications, (2) the validity results of learning media experts are worth 4.35 with very good qualifications, (3) the percentage of practicality based on teacher responses is worth 98% and student responses are worth 92.6% with very good qualifications, (4) The t-test results show the significance value in the t-test is 0.000 or p < 0.05, so H0 is helpful and H1 is accepted.